2018, resumen de un año de gratos recuerdos y éxitos para la OPQ - Chong Cáceres, Miguel Angel (2019)
The XXIII Peruvian Chemistry Olympiad was held in 2018 with a historic record of participants. On the other hand, Peruvian students had an outstanding performance in the events carried out internationally, both in Bratislava and Prague (50th International Olympiad, IChO) and in San Salvador, Republic of El Salvador (23th Iberoamerican Olympiad, OIAQ). For the first time, a Peruvian student won a silver medal at the IChO.